The effect of water restriction on anaerobic power and vertical jumping height in basketball players - Hoffman, J. R.; Stavsky, H.; Falk, B. (International Journal of Sports Medicine, 1995)
This study examined the effect of high intensity, moderate duration (40 min) exercise and water restriction on anaerobic power, vertical jumping height, and basketball shooting performance. Ten healthy male basketball players participated in two simulated '2 on 2 full-court' basketball games. Water consumption was permitted in one game (Wa) but not in the other (NWa), in a balanced cross-over design. Subjects began each game euhydrated. All jump tests (squat jump, counter movement jump, and 30 second jump test) were performed prior to, at half-time, and immediately following each game (POST). Performance was measured by both field goal (FG%) and free throw (FT%) percentages recorded during each half. Players incurred a -1.9 +/- 0.4% body weight loss during NWa. No significant differences were observed between WA and NWa in anaerobic power, squat jump, or counter movement jump. However, a 19% difference in anaerobic power (p > 0.05) was observed between Wa (36.1 +/- 4.8 W.kg-1) and NWa (30.4 +/- 6.6 W.kg-1) at POST. No significant differences were observed between Wa and NWa in both FG% and FT% however, an 8.1% decrease (p > 0.05) in FG% was seen between the first and second half during NWa. Although the decreases in anaerobic power and FG% did not reach significance, the results suggest that the combination of high intensity, moderate duration exercise, and fluid restriction might be detrimental to performance.